2021
DOI: 10.3390/cancers13020265
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Overall Survival and the Effect of Radiotherapy in Merkel Cell Carcinoma—A Retrospective Analysis of A Swedish Cohort

Abstract: Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer where Merkel cell Polyomavirus (MCPyV) contributes to the pathogenesis. In an adjuvant setting, radiotherapy (RT) is believed to give a survival benefit. The prognostic impact of sex related to MCPyV-status and adjuvant RT were analyzed in patients referred to Karolinska University Hospital. Data were collected from 113 patients’ hospital records and MCPyV analyses were made in 54 patients (48%). We found a significantly better overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…8 Clonal integration of the virus may lead to malignant transformation and has prognostic significance. 2,8,10 There is an increased reciprocal risk of MCC with other primary cancers, mainly other skin cancers and certain hematologic malignancies. 11 This may represent shared risk factors such as ultraviolet light and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Clonal integration of the virus may lead to malignant transformation and has prognostic significance. 2,8,10 There is an increased reciprocal risk of MCC with other primary cancers, mainly other skin cancers and certain hematologic malignancies. 11 This may represent shared risk factors such as ultraviolet light and immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Clonal integration of the virus may lead to malignant transformation and has prognostic significance. 2 , 8 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Although limited to Finland, it is presumed that similar situation is a common and worldwide problem, not only with MCC patients, but rather in all patients with rare cancers. Björn Andtback et al [ 9 ] review on their past experience on adjuvant radiation therapy in MCC, strengthening the previous notion that female MCC patients, regardless of MCPyV status, actually do better compared with their male counterparts. The third clinical paper by Naseri et al [ 10 ] summarize the consensus treatment recommendations by the Danish MCC expert group.…”
mentioning
confidence: 83%
“…Several small studies have shown that MCPyV-negative tumours have a worse prognosis and two recent studies showed that MCPyV-positive tumours are associated with a more favourable prognosis. A Swedish study found an increased risk of death for men with a virusnegative MCC (HR 3.6 [64]). A second study showed that MCPyV-positive tumours display longer disease-specific and recurrence-free survival in both univariate and multivariate analysis [74].…”
Section: Histological Prognostic Markers Of the Ptsmentioning
confidence: 99%